Occipital Nerve Blocks for Relief of Headaches in Patients With Ventriculoperitoneal Shunts: A Case Series. (October 2019) - Kim, Eugene; Cucchiaro, Giovanni
Pediatric patients with ventriculoperitoneal shunts commonly present with headaches. We report 7 children with ventriculoperitoneal shunts and occipital headaches who received occipital nerve blocks. Eighty-six percent of patients had a history of at least 1 ventriculoperitoneal shunt revision. Headaches improved in every patient after the block. Two patients (29%) were symptom free 11 and 12 months after the block. Four patients (57%) required repeat occipital nerve blocks. Two underwent pulsed radiofrequency ablation. No complications were noted. When patients with ventriculoperitoneal shunts present with headaches, a detailed physical examination is necessary. Persistent occipital headaches with tenderness and radiation in the path of the occipital nerves can be indicative of occipital neuralgia resulting from the shunt having crossed over the path of the greater or lesser occipital nerve. Occipital nerve blocks can help as both diagnostic and therapeutic interventions in these patients.